A Metastatic Well-differentiated Squamous Cell Carcinoma in a Patient with an Arteriovenous Fistula. Issue 2 (February 2022) - Nyeko-Lacek, Miriam; John, Hannah; Leong, Samantha; Short, Emma; Elazzabi, Tawfik; Jessop, Zita; Hemington-Gorse, Sarah
Abstract : Summary: Patients receiving hemodialysis have an increased risk of developing nonmelanoma skin cancers, such as cutaneous squamous cell carcinoma (SCC). Management of SCC usually relies on complete surgical excision of the primary tumor and may require regional lymph node dissection due to lymphatic spread. An 81-year-old man with an arteriovenous fistula (AVF) presented with an unusually aggressive metastatic well-differentiated SCC, necessitating an axillary dissection for lymph node metastasis. He had been referred for radiotherapy to complete his oncological treatment following excision of the primary SCC on his forearm. An AVF site is subjected to significant changes in circulatory pressure, leading to reduced lymphatic drainage and likely focal immunosuppression. Increased lymphatic burden, combined with repeated trauma to the fistula in an immunosuppressed patient, potentially precipitated the development of an SCC on the affected limb. The individual risk factors for SCC such as sites of chronic inflammation and repeated trauma, host immunosuppression, and renal disease are well established. This patient demonstrates the perfect storm of all these risk factors, leading to a highly malignant metastatic SCC. As the standards of renal care improve and the number of patients with AVF increases, we must remain vigilant in the management of SCCs in these patients.